Neurological Complications in Young Infants With Acute Bacterial Meningitis - Hsu, Mei-Hsin; Hsu, Jen-Fu; Kuo, Hsuan-Chang; Lai, Mei-Yin; Chiang, Ming-Chou; Lin, Ying-Jui; Huang, Hsuan-Rong; Chu, Shih-Ming; Tsai, Ming-Horng (Frontiers in Neurology, 2018)
We aimed to evaluate the occurrence, treatment, and outcomes of neurological complications after bacterial meningitis in young infants. A case series study from a retrospective cohort from two tertiary-level medical centers in Taiwan between 2007 and 2016 was conducted. Eighty-five young infants aged < 90 days with bacterial meningitis were identified. 25 (29.4%) were born at preterm. Group B Streptococcus (GBS) and Escherichia coli caused 74.1% of identified cases. Despite the majority (90.6%) initially received microbiologically appropriate antibiotics, 65 (76.5%) had experienced at least one neurological complication identified at a median of 6 days (range: 1-173) after onset of bacterial meningitis. The most common neurological complication was seizure (58.8%), followed by subdural effusion (47.1%), ventriculomegaly (41.2%), subdural empyema (21.2%), hydrocephalus (18.8%), ventriculitis (15.3%), periventricular leukomalacia (11.8%) and encephalomalacia (10.6%). Nine patients (10.6%) died (including 4 had critical discharge on request) and 29/76 (38.2%) of the survivors had major neurological sequelae at discharge. Nighteen (22.4%) received surgical intervention due to these complications. After multivariate logistic regression, initial seizure (adjusted odds ratio [aOR]: 4.76, 95% confidence interval [CI]: 1.7-13.0, P = 0.002) and septic shock (aOR: 6.04; 95% CI: 1.35-27.0, P = 0.019) were independent predictors for final unfavorable outcomes. Conclusions: Neurological complications and sequelae are common in young infants after bacterial meningitis. Patients presented with early seizure or septic shock can be an early predictor of final unfavorable outcomes and require close monitoring. Further research regarding how to improve clinical management and outcomes is warranted.